Aplikasi Web Pengelolaan Tugas Akhir pada Teknik Informatika STMIK Palangkaraya - Herkules, Herkules; Hapa, Yogi (STMIK Palangkaraya, 2018)
Development of the computer is very fast and is used in various fields of life. Usually the computer is used to produce a variety of important information in order to improve the performance of an organization, company or institution to get the job done more effectively and efficiently it is because the computer to process information quickly. To maintain the smooth, monitor, and also simplify the task of managing data majoring student thesis easily then it encourages the writer to create a research titled